Detection of Midline Shift from CT Scans to Predict Outcome in Patients with Head Injuries - Ikhlas Abdelaziz; Rowa Aljondi; Ali B Alhailiy; Mustafa Z. Mahmoud (International Journal of Biomedicine, 2021)
Background: The present study aimed to detect the degree of midline shift from CT scans and the clinical status of the patient, to evaluate the relationship between the degree of midline shift found by the CT scan and GCS score as a predictor of clinical outcome in head injury patients. Furthermore, we aimed to assess the relationship between midline shift and age, sex, and causes. Methods and Results: The study included 50 subjects (36 males and 14 females). The age range of the patients in this study was 18–95 years old (mean age of 48.34±17.02 years). The inclusion criteria were patients with traumatic brain injury (TBI) or patients evaluated for level of consciousness by a neurosurgeon. Toshiba 16 Slice CT scanner (Toshiba Medical Systems, Nasu, Japan 2003) was used to scan all patients in the supine, head first position. Contiguous 2 mm slices were obtained using the Toshiba 16-slice machine spiral technique (pitch 1.25–1.5, 0.75 s rotation time, 120 KvP, 2 mm reconstruction interval). The results indicated that the degree of midline shift in patients with brain injuries was statistically significant as a determinant of clinical outcome. It appeared that the probability of poor clinical outcome was higher when there was a combination of midline shift and other types of intracranial hemorrhage, clinical factors, such as sex, age, and GCS score, and associated injuries. The worst outcome was seen in patients with midline shift and subdural hematoma, when compared with other lesions in patients with brain injuries. Conclusion: This study suggests that the degree of midline shift may be predictive of clinical outcome in patients with head injuries.